Parents spend an average of nine hours a day providing palliative care for children at home and need to maintain an average of five life‐saving devices. (18th October 2017) - Lazzarin, P.; Schiavon, B.; Brugnaro, L.; Benini, F.
Abstract: Aim: This Italian study investigated home‐based palliative care for young children and how long it took parents to meet their needs. Methods: The study population consisted of 33 families with a child under the responsibility of the Veneto Regional Center for Pediatric Palliative Care, northern Italy, who needed medical support in at least two of the following areas: respiratory, feeding, pain and seizures. Results: The children had a mean age of 6.8 ± 4.7 years. We found that 72% of the patients needed medical devices for feeding, 36% had a tracheostomy and 55% were on mechanical ventilatory support. The children needed an average of five different life‐supporting medical appliances, and the time taken to provide for their care increased significantly with each additional appliance (p = 0.016). Their most time‐consuming daily needs were feeding (174 minutes) and support when they woke up at night (67 minutes). The average daily time that parents spent taking care of their child amounted to eight hours and 54 minutes per day. Conclusion: Parents providing palliative care for children with life‐limiting diseases spent an average of nine hours a day caring for them each day and had to maintain an average of five medical appliances.